1994
DOI: 10.1111/j.1472-765x.1994.tb00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid profile typing provides a method for the differentiation of strains of Salmonella enteritidis phage type 4 isolated in Turkey

Abstract: Five phage types have been identified in 38 strains of Salmonella enteritidis isolated in Turkey in the 20-month period June 1992-January 1994. Strains belonging to phage type 4 predominated. Within phage type 4, plasmid profile typing has proved a useful method of strain discrimination and has confirmed the identity of a putative outbreak involving canteen workers in an industrial complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The plasmid profiles of our isolates showed similarities with their report. Also several researchers reported that 55 kb plasmid, the plasmid that we identified in RTE-1, is the most dominating plasmid among Salmonella strains, especially in food-originated isolates ( Erdem et al , 1994 ; Stubbs et al , 1994 ).…”
Section: Resultsmentioning
confidence: 76%
“…The plasmid profiles of our isolates showed similarities with their report. Also several researchers reported that 55 kb plasmid, the plasmid that we identified in RTE-1, is the most dominating plasmid among Salmonella strains, especially in food-originated isolates ( Erdem et al , 1994 ; Stubbs et al , 1994 ).…”
Section: Resultsmentioning
confidence: 76%
“…are usually defined phenotypically by serotyping and antimicrobial resistance tests in microbiology laboratories of Iran. Since phenotyping data suggest the clonal diffusion of a limited number of local strains, there is a need for practical techniques to discriminate Salmonella isolates, and to evaluate the association of Salmonella strains in epidemiological studies [35]. Here, we presented the results of a molecular study of extended-spectrum cephalosporins resistant Salmonella strains isolated from pediatric patients in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…In 1994, it was reported that, among the S. enteritidis strains isolated in Ankara, the predominant phage type was PT 4 [36].…”
Section: Discussionmentioning
confidence: 99%